Teacher Performance Under the Influence of Training, Work Motivation and Teacher Competence - Adolf Bastian; Jamilah Aini Nasution; Sri Wahyuni (STAI Hubbulwathan Duri, 2022)
Teacher performance is the result of work in quality and quantity achieved by a teacher in carrying out his duties in accordance with the responsibilities given to him. The purpose of this study was to see the effect of training, work motivation and competence on the teacher's performance. The research methodology used is quantitative with multiple linear regression analysis. The sample is a teacher in a play group in Pekanbaru City. The sample are 64 teacher take by proportional random sampling. The results partially showed (1) training with t count (4,922) t table (2,4) means that training has a significant effect on teacher performance. (2) Work motivation, t count (4.171) t table (2,4) , this mean that the work motivation variable has a significant effect on teacher performance. (3) Teacher competence, t count (5,453) t table (2,4 ) . This means that the Teacher Competence variable has a significant effect on teacher performance. (4) The test results show that training, work motivation, and teacher competence together affect the performance of playgroup teachers. This is evidenced by F count (93,877) F table (2,753). Then the Adjusted R Square value is 0.873. This means that the contribution of the influence of the independent variable on the dependent variable is 87%. While the remaining 13% is influenced by other variables that are not included in this regression model. The implication is that schools seek to increase teacher motivation by providing reinforcement such as giving awards for performance that has been achieved so that teachers can work with optimal motivation.